Strategi Ketua Pasraman Dalam Meningkatkan Mutu Pembelajaran di Pasraman Askara Widya Loka - Suastini, Ni Made Duwik; Wijana, I Nyoman (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Education is an inseparable part of human life and plays an important role in the development of every era. One of the educational institutions that can support the ongoing education process is pasraman. Pasraman is a place where the teaching and learning process or education process takes place. Pasraman itself places more emphasis on self-discipline, developing noble morals and traits of being diligent, likes to work hard, restrains one's desires and likes to help others. The quality of learning in pasraman also plays an important role in realizing the goal of good and quality education, especially for Hindus. So, to achieve this quality of learning, appropriate strategies are needed that can be carried out more easily. This research aims to find out the strategies of pasraman managers, especially pasraman heads, to improve the quality of learning at pasraman so that the learning process at pasraman can take place well and be sustainable. In this way, a young generation of quality Hindus can be formed. The research method used in this research is a qualitative research method. The importance of the results of this research is as a guide for the wider community to be able to find out strategies that can be implemented to improve the quality of learning, especially in pasraman.